Pengembangan Media Evaluasi Pembelajaran Bahasa Indonesia dengan Memanfaatkan Aplikasi Daring Wordwall pada Siswa Kelas VIII A MTs Annur Al Huda Tajinan Malang - Syahrul Gunawan; Susandi Susandi; Lis Susilawati (ALFABETA: Jurnal Bahasa, Sastra, dan Pembelajarannya, 2023)
The aim of this research is to determine the development of Indonesian language learning evaluation media by utilizing the online wordwall application for class VIII A students at MTs Annur Al Huda Tajinan Malang. The subjects of this research were students at MTs Annur Al Huda Tajinan class VIII A. By using the wordwall application, it is hoped that students will not get bored during teaching and learning activities. The instrument used to collect quantitative data in this research was through a validation process. There are six steps used in this research, namely (1) needs analysis; (2) planning; (3) production; (4) product validation; (5) product evaluation; (6) limited testing. The results of the research using the wordwall application obtained an average score from material experts of 4.4 or very good category and an average score of media experts of 4.5 or very good category, while the average score of language experts was 4.6 or very good category and the results of the respondents' questionnaire calculations with an average of 4.6 or very good category. Thus, it can be concluded according to material, media, language experts and from the results of student questionnaire calculations that research into developing evaluation media using the wordwall application is suitable for use in class VIII A MTs Annur Al Huda Tajinan Malang. Keywords: media, apps, wordwall